Phylogenetic prioritization of HIV-1 transmission clusters with viral lineage-level diversification rates. Issue 1 (22nd July 2022) - Miller, Rachel L; McLaughlin, Angela; Liang, Richard H; Harding, John; Wong, Jason; Le, Anh Q; Brumme, Chanson J; Montaner, Julio S G; Joy, Jeffrey B
Abstract: Background and objectives: Public health officials faced with a large number of transmission clusters require a rapid, scalable and unbiased way to prioritize distribution of limited resources to maximize benefits. We hypothesize that transmission cluster prioritization based on phylogenetically derived lineage-level diversification rates will perform as well as or better than commonly used growth-based prioritization measures, without need for historical data or subjective interpretation. Methodology: 9822 HIV pol sequences collected during routine drug resistance genotyping were used alongside simulated sequence data to infer sets of phylogenetic transmission clusters via patristic distance threshold. Prioritized clusters inferred from empirical data were compared to those prioritized by the current public health protocols. Prioritization of simulated clusters was evaluated based on correlation of a given prioritization measure with future cluster growth, as well as the number of direct downstream transmissions from cluster members. Results: Empirical data suggest diversification rate-based measures perform comparably to growth-based measures in recreating public heath prioritization choices. However, unbiased simulated data reveals phylogenetic diversification rate-based measures perform better in predicting future cluster growth relative to growth-based measures, particularly long-term growth. Diversification rate-based measures also display advantages over growth-based measures in highlighting groups with greater future transmission events compared to random groups of the same size. Furthermore, diversification rate measures were notably more robust to effects of decreased sampling proportion. Conclusions and implications: Our findings indicate diversification rate-based measures frequently outperform growth-based measures in predicting future cluster growth and offer several additional advantages beneficial to optimizing the public health prioritization process. Lay Summary: Public health officials faced with more transmitting groups than can be immediately addressed require an efficient way to prioritize limited resources. We demonstrate that phylogenetic approximations of transmission derived from viral sequence data offer advantages over other common methods of prioritizing clusters, while meeting and frequently exceeding existing performance standards.